Moral sensitivity and the use of care technologies under Galimberti's perspective (Research, Society and Development, 2020)
This study aims to reflect on the influence of moral sensitivity and the use of technology in Galimberti's perspective. It is a theoretical and reflective study on moral sensitivity as a limit maker for the use of technologies in nursing care from the philosophical perspective of Umberto Galimberti. Two thematic axes were addressed: technology from Galimberti's philosophical perspective; moral sensitivity imposing limits on the use of technologies in nursing care. We conclude that moral sensitivity makes it possible for professionals to develop critical thinking about their practice as a nurse in the face of technological advances, so that they can make decisions for the benefit of patients with greater responsibility, without going beyond human existence and ethical and moral precepts profession.